2013
DOI: 10.3389/fpsyg.2013.00182
|View full text |Cite
|
Sign up to set email alerts
|

The role of scene type and priming in the processing and selection of a spatial frame of reference

Abstract: The selection and processing of a spatial frame of reference (FOR) in interpreting verbal scene descriptions is of great interest to psycholinguistics. In this study, we focus on the choice between the relative and the intrinsic FOR, addressing two questions: (a) does the presence or absence of a background in the scene influence the selection of a FOR, and (b) what is the effect of a previously selected FOR on the subsequent processing of a different FOR. Our results show that if a scene includes a realistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, studies examining differences in reference frame preference across languages have been inconclusive (see Tenbrink, 2007 , 2009 for discussion), suggesting that discourse and task context effects can be a much stronger influencing factor than cross-linguistic variation, particularly within closely related cultural and linguistic settings (as in our case). Indeed, reference frame choice has been shown to be affected by a range of situational influences, including the embedding of the objects in more complex and real-world scenes ( Johannsen and De Ruiter, 2013a , b ), and the communicative context in which the speaker is situated ( Galati and Avraamides, 2013 ). In our case, the task was presented in slightly different ways – on a table top in Experiment 1, as opposed to a computer screen in Experiment 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies examining differences in reference frame preference across languages have been inconclusive (see Tenbrink, 2007 , 2009 for discussion), suggesting that discourse and task context effects can be a much stronger influencing factor than cross-linguistic variation, particularly within closely related cultural and linguistic settings (as in our case). Indeed, reference frame choice has been shown to be affected by a range of situational influences, including the embedding of the objects in more complex and real-world scenes ( Johannsen and De Ruiter, 2013a , b ), and the communicative context in which the speaker is situated ( Galati and Avraamides, 2013 ). In our case, the task was presented in slightly different ways – on a table top in Experiment 1, as opposed to a computer screen in Experiment 2.…”
Section: Discussionmentioning
confidence: 99%
“… Carlson-Radvansky and Radvansky (1996) found that when the mail carrier was shown facing the mailbox, participants preferred to use in front of (intrinsic reference frame) compared with to the left of (relative reference frame) to describe the mail carrier’s position and vice versa when the mail carrier was facing away from the mailbox. The selection of a spatial reference frame is also influenced by previous discourse ( Watson et al, 2004 ; see also Schober, 1998 ; Johannsen and De Ruiter, 2013a , b ; Dobnik et al, 2014 ). For example, Watson et al (2004) found that participants were 10% more likely to use the intrinsic frame if they heard a confederate use that reference frame on the preceding trial, than when the confederate used a relative frame on the preceding trial.…”
Section: Introductionmentioning
confidence: 99%
“…This disagreement and the potential for ambiguities has led to an extensive body of psycholinguistic investigations of which factors contribute to the selection and processing of spatial FOR, mostly using monolog studies. The factors identified range from functional relations between objects (Carlson-Radvansky and Radvansky, 1996) to motion characteristics (Levelt, 1984), gravity (Friederici and Levelt, 1990), priming effects (Watson et al, 2004; Carlson and Van Deman, 2008; Johannsen and de Ruiter, 2013), scene type (Johannsen and de Ruiter, 2013), and properties of the object configuration such as the rotation of the reference object and the position of the located object (Ziegler et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Crollen and Collignon (2012) review how visuallydeprived individuals develop representations of spatial frames of reference and propose that sighted people learn to recode spatial information to an external reference frame (i.e., independent of limb/body position) as opposed to the internal reference frame (i.e., dependent on limb/body position) preferred by those without vision. Johannsen and de Ruiter (2013) observed that people's reference frame selection during scene processing is affected by the realism of the scene, with people more likely to choose an egocentric frame of reference when the background is more realistic. They suggest that greater realism results in easier perceptual simulation and therefore a greater preference for egocentric processing.…”
mentioning
confidence: 99%